The Use of Google Classroom during Pandemic - Mike Okmawati (Universitas Negeri Padang, 2020)
Educational systems worldwide has been affected by the Covid-19 pandemic, leading to the near-total closures of schools, and colleges. Most governments around the world have temporarily closed educational institutions in order to restrain the spread of Covid-19 . This requires all elements of education to adapt and to continue the teaching learning process. The Indonesia Government assigns the distance learning sistem using online learning. This is effective solution to activate classroom eventhough school have been closed to reduce the spread of covid-19. Many platforms of digital sources have been implemented by school, one of them is using Google Classroom. This research aims to get review of using Google Classroom during this pandemic. This study was library research that describe the phenemenon of using Google Classroom. The result of the research finding prove that it is effective to use this platform. It is one way to be considered by the schools and teachers to provide students by e learning that can be attracted for the students, while the process of teacher learning move to virtual classes. Key words: Google Classroom, Pandemic, Covid-19, Online Learning